2013
DOI: 10.2478/intox-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of exploratory behaviour in VPA rats: animal model of autism

Abstract: Autism is a neurodevelopmental disorder with multifactorial aetiology, represented as impairment in social behaviour, communication and the occurrence of repetitive activities, which can be observed in the early life. The core features are frequently accompanied by other manifestations, including limited environmental exploration. The aim of the presented study, realised on an animal model of autism – VPA rats, i.e. animals prenatally affected with valproic acid on gestation day 12.5, was to investigate the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Clinical studies have shown that exposure to VPA in utero is associated with birth defects, cognitive deficits, and increased risk of autism (Nadebaum et al, 2011 ). Our data demonstrate that VPA-treated rats also exhibited autism-like behaviors and deficits in the reflex development, motor coordination, auditory and visual development, which are consistent with clinical symptoms of patients with autism and the findings of other labs’ using VPA-induced rodent models of autism (Snow et al, 2008 ; Mehta et al, 2011 ; Favre et al, 2013 ; Olexová et al, 2013 , 2016 ; Ha et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…Clinical studies have shown that exposure to VPA in utero is associated with birth defects, cognitive deficits, and increased risk of autism (Nadebaum et al, 2011 ). Our data demonstrate that VPA-treated rats also exhibited autism-like behaviors and deficits in the reflex development, motor coordination, auditory and visual development, which are consistent with clinical symptoms of patients with autism and the findings of other labs’ using VPA-induced rodent models of autism (Snow et al, 2008 ; Mehta et al, 2011 ; Favre et al, 2013 ; Olexová et al, 2013 , 2016 ; Ha et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…It is well known that prenatal exposure to valproic acid could result in neurodevelopmental disorder during adolescence (29). The offspring of pregnant Wistar rats that received an intraperitoneal injection of 600 mg/kg valproic acid demonstrated declined spontaneous movements during puberty and maturity compared with rat offspring not treated with valproic acid (30). In our work, high concentration (500 μM) of valproic acid significantly reduced the spontaneous movement of zebrafish larvae under both light and dark conditions.…”
Section: Discussionsupporting
confidence: 54%
“…The age at which offspring were tested resulted in a number of relevant outcomes, likely specific to VPA exposure. Interestingly, older ages in the VPA groups had decreased social [66] and total [67] exploration than younger VPA-exposed rodents. Older VPA-exposed rodents had a lower discrimination index in the novel object recognition test compared to younger VPA rodents [68].…”
Section: Age Differencesmentioning
confidence: 91%